CBFB-MYH11 Fusion Sequesters RUNX1 in Cytoplasm to Prevent DNMT3A Recruitment to Target Genes in AML - Liu, Peng; Liu, Jin-Pin; Sun, Si-Jia; Gao, Yun; Ai, Yingjie; Chen, Xiufei; Sun, Yiping; Zhou, Mengyu; Liu, Yun; Xiong, Yue; Yuan, Hai-Xin (Frontiers in Cell and Developmental Biology, 2021)
A growing number of human diseases have been found to be associated with aberrant DNA methylation, including cancer. Mutations targeting genes encoding DNA methyltransferase (DNMT), TET family of DNA demethylases, and isocitrate dehydrogenase (IDH1, IDH2) that produce TET inhibitory metabolite, 2-hyoxyglutarate (2-HG), are found in more than half of acute myeloid leukemia (AML). To gain new insights into the regulation of DNA de/methylation and consequence of its alteration in cancer development, we searched for genes which are mutated in a manner that is linked with gene mutations involved in DNA de/methylation in multiple cancer types. We found that recurrent CBFB-MYH11 fusions, which result in the expression of fusion protein comprising core-binding factor β (CBFB) and myosin heavy chain 11 (MYH11) and are found in 6~8% of AML patients, occur mutually exclusively with DNMT3A mutations. Tumors bearing CBFB-MYH11 fusion show DNA hypomethylation patterns similar to those with loss-of-function mutation of DNMT3A. Expression of CBFB-MYH11 fusion or inhibition of DNMT3A similarly impairs the methylation and expression of target genes of Runt related transcription factor 1 (RUNX1), a functional partner of CBFB. We demonstrate that RUNX1 directly interacts with DNMT3A and that CBFB-MYH11 fusion protein sequesters RUNX1 in the cytoplasm, thereby preventing RUNX1 from interacting with and recruiting DNMT3A to its target genes. Our results identify a novel regulation of DNA methylation and provide a molecular basis how CBFB-MYH11 fusion contributes to leukemogenesis.